A facile method for the preparation of bifunctional Mn:ZnS/ZnS/Fe3O4 magnetic and fluorescent nanocrystals - Labiadh, Houcine; Ben Chaabane, Tahar; Sibille, Romain; Balan, Lavinia; Schneider, Raphaël (Beilstein Journal of Nanotechnology, 2015)
Bifunctional magnetic and fluorescent core/shell/shell Mn:ZnS/ZnS/Fe3O4 nanocrystals were synthesized in a basic aqueous solution using 3-mercaptopropionic acid (MPA) as a capping ligand. The structural and optical properties of the heterostructures were characterized by X-ray diffraction (XRD), dynamic light scattering (DLS), transmission electron microscopy (TEM), UV–vis spectroscopy and photoluminescence (PL) spectroscopy. The PL spectra of Mn:ZnS/ZnS/Fe3O4 quantum dots (QDs) showed marked visible emission around 584 nm related to the 4T1 → 6A1 Mn2+ transition. The PL quantum yield (QY) and the remnant magnetization can be regulated by varying the thickness of the magnetic shell. The results showed that an increase in the thickness of the Fe3O4 magnetite layer around the Mn:ZnS/ZnS core reduced the PL QY but improved the magnetic properties of the composites. Nevertheless, a good compromise was achieved in order to maintain the dual modality of the nanocrystals, which may be promising candidates for various biological applications.
Keywords: aqueous synthesis; bifunctional nanocrystals; magnetite; Mn-doped ZnS; quantum dots

(untitled) - Bawendi, M. G.; Steigerwald, M. L.; Brus, L. E. (Annu. Rev. Phys. Chem., 1990)

(untitled) - Alivisatos, A. P. (Science, 1996)

(untitled) - Medintz, I. L.; Uyeda, H. T.; Goldman, E. R.; Mattoussi, H. (Nat. Mater., 2005)

(untitled) - Michalet, X.; Pinaud, F. F.; Bentolilo, L. A.; Tsay, J. M.; Doose, S.; Li, J. J.; Sundaresan, G.; Wu, A. M.; Gambhir, S. S.; Weiss, S. (Science, 2005)

(untitled) - Geszke, M.; Murias, M.; Balan, L.; Medjahdi, G.; Korczynski, J.; Moritz, M.; Lulek, J.; Schneider, R. (Acta Biomater., 2011)

(untitled) - Coe, S.; Woo, W.-K.; Bawendi, M.; Bulović, V. (Nature, 2002)

(untitled) - Sun, Q.; Wang, Y. A.; Li, L. S.; Wang, D.; Zhu, T.; Xu, J.; Yang, C.; Li, Y. (Nat. Photonics, 2007)

(untitled) - Kamat, P. V. (J. Phys. Chem. C, 2008)

(untitled) - Gao, J.; Gu, H.; Xu, B. (Acc. Chem. Res., 2009)

(untitled) - Hao, R.; Xing, R.; Xu, Z.; Hou, Y.; Gao, S.; Sun, S. (Adv. Mater., 2010)

(untitled) - Lee, I. S.; Lee, N.; Park, J.; Kim, B. H.; Yi, Y.-W.; Kim, T.; Kim, T. K.; Lee, I. H.; Paik, S. R.; Hyeon, T. (J. Am. Chem. Soc., 2006)

(untitled) - Jeong, U.; Teng, X.; Wang, Y.; Yang, H.; Xia, Y. (Adv. Mater., 2007)

(untitled) - Xu, W.; Kattel, K.; Park, J. Y.; Chang, Y.; Kim, T. J.; Lee, G. H. (Phys. Chem. Chem. Phys., 2012)

(untitled) - Kobayashi, T. (Biotechnol. J., 2011)

(untitled) - Gu, H.; Zheng, R.; Zhang, X. X.; Xu, B. (J. Am. Chem. Soc., 2004)

(untitled) - Qao, J.; Zhang, W.; Huang, P.; Zhang, B.; Zhang, X.; Xu, B. (J. Am. Chem. Soc., 2008)

(untitled) - Chekina, N.; Horák, D.; Jendelová, P.; Trchová, M.; Beneš, M. J.; Hrubý, M.; Herynek, V.; Turnovcová, K.; Syková, E. (J. Mater. Chem., 2011)

(untitled) - Corr, S. A.; Rakovich, Y. P.; Gun’ko, Y. K. (Nanoscale Res. Lett., 2008)

(untitled) - Koole, R.; Mulder, W. J. M.; van Schooneveld, M. M.; Strijkers, G. J.; Meijerink, A.; Nicolay, K. (Wiley Interdiscip. Rev.: Nanomed. Nanobiotechnol., 2009)

(untitled) - Gao, J.; Zhang, B.; Gao, Y.; Pan, Y.; Zhang, X.; Xu, B. (J. Am. Chem. Soc., 2007)

(untitled) - Kim, H.; Acherman, M.; Balet, L. P.; Hollingsworth, J. A.; Klimov, V. I. (J. Am. Chem. Soc., 2004)

(untitled) - Kwon, K.-W.; Shim, M. (J. Am. Chem. Soc., 2005)

(untitled) - Geszke-Moritz, M.; Piotrowska, H.; Murias, M.; Balan, L.; Moritz, M.; Lulek, J.; Schneider, R. (J. Mater. Chem. B, 2013)

(untitled) - Kolmykov, O.; Coulon, J.; Lalevée, J.; Alem, H.; Medjahdi, G.; Schneider, R. (Mater. Sci. Eng., C, 2014)

(untitled) - Pradhan, N.; Goorsky, D.; Thessing, J.; Peng, X. (J. Am. Chem. Soc., 2005)

Match! Phase Identification from Powder Diffraction

(untitled) - Sun, Y.-k.; Ma, M.; Zhang, Y.; Gu, N. (Colloids Surf., A, 2004)

(untitled) - Monazam, E. R.; Breault, R. W.; Siriwardane, R. (Ind. Eng. Chem. Res., 2014)

(untitled) - Ling, Y.; Wang, G.; Wang, H.; Yang, Y.; Li, Y. (ChemSusChem, 2014)

(untitled) - Denzler, D.; Olschewski, M.; Sattler, K. (J. Appl. Phys., 1998)

(untitled) - Erwin, S. C.; Zu, L.; Haftel, M. I.; Efros, A. L.; Kennedy, T. A.; Norris, D. J. (Nature, 2005)

(untitled) - Balti, I.; Smiri, L. S.; Rabu, P.; Gautron, E.; Viana, B.; Jouini, N. (J. Alloys Compd., 2014)

(untitled) - Nadeem, K.; Krenn, H.; Traussnig, T.; Würschum, R.; Szabó, D. V.; Letofsky-Papst, I. (J. Magn. Magn. Mater., 2011)

(untitled) - Tadic, M.; Citakovic, N.; Panjan, M.; Stanojevic, B.; Markovic, D.; Jovanovic, D.; Spasojevic, V. (J. Alloys Compd., 2012)

(untitled) - Hill, A. H.; Jiao, F.; Bruce, P. G.; Harrison, A.; Kockelmann, W.; Ritter, C. (Chem. Mater., 2008)

(untitled) - Liu, C.; Zou, B.; Rondinone, A. J.; Zhang, Z. J. (J. Am. Chem. Soc., 2000)

(untitled) - Labiadh, H.; Chaabane, T. B.; Piatkowski, D.; Mackowski, S.; Lalevée, J.; Ghanbaja, J.; Aldeek, F.; Schneider, R. (Mater. Chem. Phys., 2013)